'Making Strange': Discourse Analysis Tools for Teaching Critical Development Studies. (July 2022) - Gasper, Des
Critical development studies require not just a critical attitude, but also usable tools. This article suggests some forms of discourse analysis that can add substance to critical development studies' aspirations and that can yet be learnt and used by students without specialist background. Central are tools for 'making strange' (defamiliarization), so that we view both texts and social realities in a fresh independent way and start to discern better their blindspots, and our own. The article presents accessible yet helpful forms of text analysis, argumentation analysis and content analysis that contribute in required processes of defamiliarization and reconstruction.